Strategic Immigration Policies and Welfare in Heterogeneous Countries - Masahisa Fujita; Shlomo Weber (Fondazione Eni Enrico Mattei (FEEM), 2004)
In this paper we consider a model with two industrialised countries and immigrants that come from the rest of the world. The countries are distinguished on the basis of three parameters: population size, bias towards immigrants, and production complementarity between native population and immigrants. We consider a non-cooperative game where each country makes a strategic choice of its immigration quotas. We first show that our game admits a unique pure strategy Nash equilibrium and then study the welfare implications of countries' choices. It turns out that a county with a higher degree of production complementarity and a higher level of tolerance towards immigrants would allow a larger immigration quota and achieve a higher welfare level. Our results call for coordinated and harmonised immigration policies that may improve the welfare of both countries.
Keywords: C72; F22; O3; R1; 330; Immigration quotas; Heterogeneity; Production complementarity; Welfare; Policy Harmonisation; Migrationspolitik; Wohlfahrtsanalyse; Theorie; Industrieländer; Nichtkooperatives Spiel